Social Comparison Orientation and Social Media Use by Brazilian Accounting Students - Meurer, Alison Martins; Costa, Flaviano (Advances in Scientific and Applied Accounting, 2024)
Purpose: Social Comparison Orientation is a psychological and behavioral predisposition that is rooted in individuals' uncertainties about their own abilities and opinions. The frequent and inappropriate use of social networks, in addition to enabling social comparison, may lead to the maximization of this behavior, which is sometimes harmful to the individual. This research sought to identify how accounting students’ social comparison orientation changes according to the characteristics of social media use. Methodology: The responses were collected from an online survey of accounting students. 502 valid responses were obtained and to verify and compare social comparison orientation based on the characteristics of social media use, the statistical tests multigroup confirmatory factor analysis, and MANOVA were used. Results or Discussion: MANOVA pointed out significant differences in the clusters of following celebrities and influencers on social media to compare abilities and opinions and in the number of friends to compare opinions. Conclusion: The engagement with posts from influencers and celebrities related to the facets of Social Comparison Orientation (SCO) may stem from the profile of accounting professionals described in the literature, who tend to be introverted and may seek for socially accepted patterns of behavior through social media. Therefore, understanding how the characteristics of social media usage affect social comparison behavior can be valuable for promoting a more conscious use of these digital tools.